2023
DOI: 10.1088/1402-4896/ad03c0
|View full text |Cite
|
Sign up to set email alerts
|

Defect analysis and microstructural characterization of zinc-substituted cadmium oxide nanocrystallites by positron annihilation and supplementary methods

Maudud Ahmed,
Shubharaj Mukherjee,
Tukai Singha
et al.

Abstract: Pure and zinc-doped cadmium oxide nanocrystallites of sizes in the range 25 nm to 16 nm are synthesized by adopting a chemical precipitation method and by varying the doping concentration from 0.0 to 0.25 at.%. The decrease in nanocrystallite sizes with increasing substitution is expected from the smaller ionic radii of Zn2+. But more revealing is the interfacial defects formation at higher concentration of doping, which is attributed to the dissimilar crystalline structure of ZnO and CdO. X-ray diffraction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A direct and unambiguous identification of native vacancy type defects and/or dipolar vacancy complexes in TlGaSe 2 layered crystal is still an open question. It has been demonstrated that the native isolated vacancies as well as vacancy complexes in some wide-bandgap semiconductor materials can be directly identified using a positron annihilation lifetime spectroscopy method [64,65]. To date, identification of isolated chalcogen vacancies (monovacancies), which could be an abundant defect in all two-dimensional TlMX 2 wide-bandgap dichalcogenides, or metal-chalcogen vacancy complexes at the atomic level is also possible by performing a combination of experiments, such as x-ray photoelectron spectroscopy, Auger electron spectroscopy, and electron paramagnetic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…A direct and unambiguous identification of native vacancy type defects and/or dipolar vacancy complexes in TlGaSe 2 layered crystal is still an open question. It has been demonstrated that the native isolated vacancies as well as vacancy complexes in some wide-bandgap semiconductor materials can be directly identified using a positron annihilation lifetime spectroscopy method [64,65]. To date, identification of isolated chalcogen vacancies (monovacancies), which could be an abundant defect in all two-dimensional TlMX 2 wide-bandgap dichalcogenides, or metal-chalcogen vacancy complexes at the atomic level is also possible by performing a combination of experiments, such as x-ray photoelectron spectroscopy, Auger electron spectroscopy, and electron paramagnetic resonance.…”
Section: Discussionmentioning
confidence: 99%